Test of Different Mesh Size on The Quality of Coffee Bean in Multifucer Grinder - Johanes Panggabean; Ainun Rohana; Adian Rindang; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was aimed to test the effect of different mesh sizes on the quality of coffee beans in the multifucer grinder using roasted arabica and robusta coffee beans. The parameters measured were the effective capacity of the equipment, the percentage of material that passed the sieve, coffee powder moisture content, percentage of soluble coffee powder in water and organoleptic tests. The results showed that the best effective capacity was 35.56 kg/hour for the treatment of robusta coffee with 250 mesh sieve, the percentage of material that passed the sieved was 93.33% for Arabica coffee at 150 mesh sieve. The best coffee powder water content was 2.43% for Arabica coffee at treatment with 250 mesh sieve. The best percentage of soluble coffee powder was 33% at 250 mesh sieve. The best aroma was 3.9, which means that the aroma was very typical for treatment of 250 mesh sieve. The best taste was 3.46, which means the taste was typical for Arabica coffee at 250 mesh sieve. The quality of coffee powder produced from the grinding was in compliance with the quality standards of Indonesia. Key words: multifucer, sieve, mesh, robusta coffee, arabica coffee.